VOCAL PERFORMANCE TECHNIQUE AND THE PROCESS OF SHAPING IT - Yuldashov Asliddin Pardaevich (Journals Park Publishing, 2026)
This article provides a comprehensive analysis of vocal performance technique and the multidimensional process of shaping it in both academic and traditional singing contexts. The study examines physiological, acoustic, pedagogical, artistic, psychological, and stylistic components that influence the development of a vocalist’s skill. Special attention is given to breath management, phonation, resonance strategies, diction, expressive interpretation, and the integration of emotional intelligence with technical control. The article further explores methods of vocal training, the role of sensory feedback, and the long-term formation of vocal identity, emphasizing how systematic pedagogical practices lead to stable, healthy, and artistically mature vocal performance.
Keywords: Vocal technique, phonation, resonance, vocal pedagogy, breath support, articulation, vocal timbre, performance training.